The taxonomy of Cyrtodactylus consobrinus (Peters, 1871) (Squamata, Gekkonidae) and the description of a new species from the Thai-Malay Peninsula - L. Lee Grismer; Amanda Kaatz; Jesse L. Grismer; Eddie Nguyen; Jeren J. Grergory; Perry L. Wood Jr.; Matthew L. Murdoch; Shahrul Anuar Mohd Sah; Chan Kin Onn; Muhamad A. Muin; Parinya Pawangkhanant; Chatmongkon Suwannapoom; et al. (Pensoft Publishers, 2025)
Phylogenetic analyses based on 1459 base pairs of the mitochondrial gene ND2 and its flanking tRNAs indicate that Cyrtodactylus consobrinus from the type locality in Sarawak, East Malaysia (Borneo) and C. consobrinus from Peninsular Malaysia are not conspecific. Both populations as well as C. hutan from East Malaysia form a strongly supported monophyletic group even though their relationships to one another remain unresolved. Cyrtodactylus consobrinus from peninsular Malaysia is described herein as the new species C. peninsular is sp. Nov. whose type locality is Gunung Belumut, Johor State. Cyrtodactylus peninsular is sp. Nov. is diagnosable from all other species in the Malayan us group by having statistically different morpho spatial positions in multiple factor analyses (MFA) based on size-corrected morphometric and meristic characters. ANOVA analyses of these characters recovered significantly different mean values be- tween C. peninsular is sp. Nov. and varying combinations of all other Malayan us group species across several size-corrected morphometric and meristic characters. Genetic variation within C. peninsular is sp. Nov. is geographically structured across six well sup- ported monophyletic mitochondrial lineages bearing an uncorrected pairwise sequence divergence ranging from 0.97–4.5%. Despite its well supported phylogeographic structure, PCAs and ANOVAs recovered statistically weak morphological separation among the lineages and as such, all are considered conspecific pending a genomic analysis. The phylogeographic structure within the forest-dwelling C. peninsular is sp. Nov. is quite similar to that of the stream-adapted ranid frog genus Amo lops and less so to that of the microhabitat specialists of the C. pulchellus group and the forest generalist C. quadrivirgatus, all of whom are sympatric across Peninsular Malaysia.